(untitled) (Mediscope, 2017)
The risk of gallstones is thought to increase with number of pregnancies. Cholesterol gallstones are more prevalent in women than men and primarily related to sex steroids, particularly progesterone. During pregnancy there are changes in bile composition and gallbladder motility that promote gallstone formation. This study was conducted to determine incidence and outcome of pregnancy related biliary sludge and gallstone formation. Two hundred and nine consecutive expectant women were evaluated by ultrasonography at 1st trimester, 3rd trimester and at 4-6 weeks after delivery. Socio-demographic, medical and obstetrical history were taken and recorded. Incidence of gallstone and sludge formation were found 5.7% and 2.9%, respectively. The results suggest that pregnancy may be a risk factor for gallstone and biliary sludge formation. Mediscope Vol. 4, No. 2: Jul 2017, Page 21-24